Математичні моделі пристроїв для обчислення дробово-раціональних функцій - Селезньова, Є. О. (ХНУРЕ, 2019)
The project analyzes and uses the method of gradual approximation of function reproduction. This model can be used to create a device that can be used in automatic control systems, modeling and control, information measuring systems as functional converters of various physical quantities derived from information sensors.